2014
DOI: 10.1890/es14-00217.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecohydrology with unmanned aerial vehicles

Abstract: Abstract. High-resolution characterizations and predictions are a grand challenge for ecohydrology.Recent advances in flight control, robotics and miniaturized sensors using unmanned aerial vehicles (UAVs) provide an unprecedented opportunity for characterizing, monitoring and modeling ecohydrologic systems at high-resolution (,1 m) over a range of scales. How can the ecologic and hydrologic communities most effectively use UAVs for advancing the state of the art? This Innovative Viewpoints paper introduces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 70 publications
0
61
0
2
Order By: Relevance
“…Further such case studies are summarized by Birdsong et al (2015). In addition, UAS have proven useful for collecting fine-scale hydrological data (Vivoni et al 2014;Spence and Mengistu 2015).…”
Section: Wetland Riparian and Coastal Habitatsmentioning
confidence: 99%
“…Further such case studies are summarized by Birdsong et al (2015). In addition, UAS have proven useful for collecting fine-scale hydrological data (Vivoni et al 2014;Spence and Mengistu 2015).…”
Section: Wetland Riparian and Coastal Habitatsmentioning
confidence: 99%
“…The use of UAVs in earth science research is undergoing rapid expansion with numerous researchers exploiting the financial and spatiotemporal resolution benefits of UAV technology (Ahmad, 2011;Colomina and Molina, 2014;D'Oleire-Oltmanns et al, 2012;Hardin and Jensen, 2011;Koh and Wich, 2012;Vivoni et al, 2014;Watts et al, 2012). A few projects have utilised UAV platforms in mountainous glaciated regions (Bhardwaj et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, this rapidly emerging technology offers the opportunity to reveal new insights into hydrological, geomorphological, atmospheric, and biotic processes, and represents a game-changing sensing platform. In a recent contribution, Vivoni et al (2014) reviewed the application of UAVs for eco-hydrology and suggested that UAV remote sensing can fundamentally change how ecohydrologic science is conducted. This same is true for hydrology.…”
Section: Unmanned Aerial Vehiclesmentioning
confidence: 99%